2019
DOI: 10.1371/journal.pone.0225309
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of microbial communities in floral nectar of two night-blooming plants of the Sonoran Desert

Abstract: Nectar-inhabiting microbes are increasingly appreciated as important components of plant-pollinator interactions. We quantified the incidence, abundance, diversity, and composition of bacterial and fungal communities in floral nectar of two night-blooming plants of the Sonoran Desert over the course of a flowering season: Datura wrightii (Solanaceae), which is pollinated by hawkmoths, and Agave palmeri (Agavaceae), which is pollinated by bats but visited by hawkmoths that forage for nectar. We examined the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 50 publications
1
31
1
Order By: Relevance
“…Differences between hosts could largely be attributed to the presence of rare taxa, while the most abundant taxa were shared between hosts. Unlike our results, previous studies in flower microbiomes have found significant differences in the bacterial community composition across host species (von Arx et al, 2019;Gaube et al, 2020;Junker et al, 2011), even when the hosts were in the same genus (Wei & Ashman, 2018). These studies, however, com- Moreover, we did not observe differences between the top and bottom surfaces of the petal, except for presence-absence data (see "Sørensen"; Table A2) where the top surface of the petal had higher ASV richness than the bottom (Figure 4, Figure A3).…”
Section: F I G U R Econtrasting
confidence: 99%
“…Differences between hosts could largely be attributed to the presence of rare taxa, while the most abundant taxa were shared between hosts. Unlike our results, previous studies in flower microbiomes have found significant differences in the bacterial community composition across host species (von Arx et al, 2019;Gaube et al, 2020;Junker et al, 2011), even when the hosts were in the same genus (Wei & Ashman, 2018). These studies, however, com- Moreover, we did not observe differences between the top and bottom surfaces of the petal, except for presence-absence data (see "Sørensen"; Table A2) where the top surface of the petal had higher ASV richness than the bottom (Figure 4, Figure A3).…”
Section: F I G U R Econtrasting
confidence: 99%
“…These 164 other-possibly environmental bacterial OTUs were not amplified in the extraction blank and non‐template amplification controls (Supplementary Table S4 ), excluding their origin from laboratory work contaminations 45 . Although the acquisition of environmental bacteria may have been resulted from stochastic processes (e.g., nectar and pollen bacterial diversity 46 , 47 ), their assembly was significantly affected by gut compartmentalization in terms of composition (i.e., niche partitioning; F 3,16 = 4.4, p = 0.001; Figs. 2 f and 4 ; n = 190, p < 0.0001, R 2 = 0.14; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, adult forager honeybees were collected from the front of the hive following exposure to the natural environment (i.e., flowered prairie), thereby enabling the recruitment of main core bacteria from the hive and contact among mates and environmental bacteria during harvest 3 , 29 , 44 . Such recruitment processes are affected by the surrounding environment and pollination landscape (e.g., microbiome variation in nectar, pollen, and hive materials 46 , 58 ), resulting in strong variation among the frequencies and biodiversity of bacteria associated with honeybees 5 , 21 , 29 , 43 . Although we anticipated that the type of environmental bacteria (non-gut bacteria, such as Actinomycetales , Alphaproteobacteria , Enterobacteriaceae , Pseudomonadales , Firmicutes, and Xanthomonadaceae 43 , 58 ) would vary depending on environmental conditions (such as location, season, food source, and climate), their recruitment and distribution was determined by the interaction between the physico-chemical conditions and biological network of the honeybee gut.…”
Section: Resultsmentioning
confidence: 99%
“…Plants are the preferred habitats for yeasts and they include nectars, flowers, fruits, decaying tissues, and tree saps [ 3 , 4 ]. These plant parts also attract insects that not only help the distribution of yeasts to different habitats but also play a great role in diversifying the yeast communities in flowers making the yeast diversity seasonal since the pollinating insects are mostly seasonal [ [4] , [5] , [6] ]. In addition, yeasts are widely distributed in the soil [ 1 ].…”
Section: Introductionmentioning
confidence: 99%